Performance of soybean (Glycine max L.) genotypes under delayed monsoon conditions in transitional tract of Dharwad: Performance of soybean (Glycine max L.) genotypes under delayed monsoon conditions in transitional tract of Dharwad - BOMNGAM KARLO; J A HOSMATH (Journal of Oilseeds Research, 2020)
The experimental results indicated that genotype DSb-32 recorded significantly higher seed yield (25.04 q/ha) and B:C ratio (2.75) concluding that the genotype DSb-32 proved superior under delayed onset monsoon conditions for realizing optimal yield and returns.